2021
DOI: 10.1007/s10554-021-02248-6
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of calcification distribution in severe tricuspid aortic valve stenosis

Abstract: We investigated aortic valve calcification (AVC) distribution and predictors for leaflet calcification patterns in patients with severe tricuspid aortic valve stenosis undergoing transcatheter aortic valve replacement (TAVR). Patients undergoing routine multi-sliced computed tomography (MSCT) for procedural planning were enrolled. MSCT data were transferred to a dedicated workstation for evaluation (3mensio Structural Heart™, Pie Medical Imaging BV, Maastricht, The Netherlands) and analyzed. Participants were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
1
1
0
1
Order By: Relevance
“…Although in the present study, under-expansion could not be directly evaluated, under-expansion was presumed due to a smaller post-procedure EOA value in the leaflet thrombosis patients. The leaflet sections where thickening occurred were mostly in the sequence of NCC-RCC-LCC, which was the same order reported in a prior study ( 29 ) and the same order shown to have significant calcium ( 30 ). Regional under-expansion of stent was reportedly associated with leaflet thrombosis in a study by Fuchs A et al and a post-mortem study ( 29 , 31 ).…”
Section: Discussionsupporting
confidence: 83%
“…Although in the present study, under-expansion could not be directly evaluated, under-expansion was presumed due to a smaller post-procedure EOA value in the leaflet thrombosis patients. The leaflet sections where thickening occurred were mostly in the sequence of NCC-RCC-LCC, which was the same order reported in a prior study ( 29 ) and the same order shown to have significant calcium ( 30 ). Regional under-expansion of stent was reportedly associated with leaflet thrombosis in a study by Fuchs A et al and a post-mortem study ( 29 , 31 ).…”
Section: Discussionsupporting
confidence: 83%
“…La presencia de RPV se ha relacionado con la calcificación valvular y su distribución, que generalmente es asimétrica, más importante en la valva y seno no coronariano en la mayoría de los pac. (15) En diferentes estudios se analizó la presencia de calcio y su volumen en la zona de implante (16,17) y se demostró que la asimetría de la calcificación se relaciona con RPV. (18) Además, algunos autores analizaron la presencia de calcio en el tracto de salida del ventrículo izquierdo.…”
Section: Resultsunclassified
“…With the extension of TAVR to younger patients, rates of subclinical leaflet thickening have been increasing [8][9][10]. Many studies [5,6] have shown rates of leaflet thrombosis are linked to unfavorable TAVR deployment parameters such as eccentric deployments [11] or reduced valve performance due to heavy patient calcification [12], as well as anatomical features such as large sinus of Valsalva leading to increased stagnation [13].…”
Section: Introductionmentioning
confidence: 99%